2010
DOI: 10.1097/qai.0b013e3181edaaf5
|View full text |Cite
|
Sign up to set email alerts
|

Dried Blood Spot HIV-1 RNA Quantification Using Open Real-Time Systems in South Africa and Burkina Faso

Abstract: There is an urgent need to assess the accuracy/feasibility of using dried blood spots (DBS) for monitoring of HIV-1 viral load in resource-limited settings. A total of 892 DBS from HIV-1-positive pregnant women and their neonates enrolled in the Kesho Bora prevention of mother-to-child transmission trial conducted in Durban (South Africa) and Bobo-Dioulasso (Burkina Faso) between May 2005 and July 2008 were tested for HIV-1 RNA. The combination Nuclisens extraction method (BioMérieux)/Generic HIV Viral Load as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…The use of DBS with commercial and in-house VL assays has already been shown to have some success (20,21). Preliminary data using spiked whole-blood samples have shown that the current VFA performs well with DBS but with reduced sensitivity compared to plasma samples, which has been previously described (20,22).…”
Section: Discussionmentioning
confidence: 98%
“…The use of DBS with commercial and in-house VL assays has already been shown to have some success (20,21). Preliminary data using spiked whole-blood samples have shown that the current VFA performs well with DBS but with reduced sensitivity compared to plasma samples, which has been previously described (20,22).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, several RLC programs have started to use DBS to expand access to HIV VL and genotypic drug resistance testing (12)(13)(14). It is thus important to evaluate to what extent this approach is reliable compared to using plasma, also considering the existing infrastructure and personnel.…”
mentioning
confidence: 99%
“…While standard laboratory platforms typically retain high accuracy when utilising the recommended threshold of 1 000 copies/ mL, both DBS and POC devices may need to utilise a higher limit (3 000 -5 000 copies/mL has been suggested) until better sensitivity is established at the lower limit of detection. [2] A study by Viljoen et al [3] in Durban using DBS HIV-1 RNA testing appeared accurate and feasible down to approximately 3 000 copies/mL. In a study conducted in southern India by Neogi et al, [4] DBS HIV-1 RNA testing revealed 100% sensitivity and specificity at 5 000 copies/mL, but only 50% sensitivity with 100% specificity at 1 000 copies/mL.…”
mentioning
confidence: 99%
“…[2] A study by Viljoen et al [3] in Durban using DBS HIV-1 RNA testing appeared accurate and feasible down to approximately 3 000 copies/mL. In a study conducted in southern India by Neogi et al, [4] DBS HIV-1 RNA testing revealed 100% sensitivity and specificity at 5 000 copies/mL, but only 50% sensitivity with 100% specificity at 1 000 copies/mL. Most recently, when Kleshik et al [5] quantified HIV-1 RNA in single 50 µL DBSs and limited incubation time prior to sample preparation to 30 minutes, a limit of detection of 866 copies/mL was reported.…”
mentioning
confidence: 99%